Impact of Green IS, Service Innovation and Customer Experience in influencing Customer Satisfaction and Environmental Performance - Mihardjo, Leonardus W.W.; Sasmoko, Sasmoko; Alamsjah, Firdaus; Elidjen, Elidjen (International Journal of Energy Economics and Policy, 2019)
The current study is focused to empirically identify the relationship between digitalization, customer experience, satisfaction, and performance in the hotel industry of Indonesia. In doing so, the authors seek to examine the technological antecedents of customer experience (CUE) by examining the role of green information systems (GIS) and service innovation (SEI). Moreover, the study also aims to investigate the association of SEI and GIS with customer satisfaction (CUS) and hotels environmental performance (ENP). The novelty of the present study lies in identifying and testing the joint effects of the studied variables in improving the understanding of customer satisfaction and environmental performance in an existing complex environment. The results of PLS-SEM confirm that customer experience and environmental performance have a positive and significantly influenced by the green information system. Moreover, the results further suggested that customer experience and customer satisfaction have significantly and positively impacted by service innovation. Finally, the results of PLS-SEM confirm that environmental performance and customer satisfaction have significantly and positively impacted by customer experience in multinational firms in Indonesia. Keywords: Green information system, service innovation, customer satisfaction, Indonesia. JEL Classifications: L8, O3 DOI: https://doi.org/10.32479/ijeep.8371